(untitled) (Revista horizonte, 2021)
Introduction. Although the wide variability to exercise has been studied, there are few studies that have addressed the existence of this phenomenon using different exercise modalities. Objective: To investigate which including 20-cardiometabolic or performance variables respond well (improve) after intermittent exercise (HIT), strength (RT) or combined exercise (CT). Methodology: Forty-five adult women with insulin resistance were distributed in four groups (HIT, 39.2 ± 9.5 years, BMI, 29.3 ± 3.3, N = 14), (RT, 33.9 ± 9.3 years, BMI, 29.4 ± 5.5, N = 8), (CT, 43.3 ± 8.1 years,BMI, 29.1 ± 2.9, N = 10); and a control group (CG, 40.1 ± 11.4 years, BMI, 28.3 ± 3.5, N = 13). Body composition variables (N = 9), cardiovascular (N = 3), metabolic (N = 3), and performance variables (N = 5 variables) were measured before and after the intervention, responders and non-responders were reported. Results: The RT exercise showed a lower number of subjects NRs, versus HIT or CT. Significant changes were recorded in body composition, metabolic parameters and endurance performance. Conclusion: Considering 20 variables as objective, and including 3 types of exercise, independently of the volume and frequency of the exercise, the RT exercise offers a greater capacity to improve 20 variables, offering a smaller number of subjects NRs. Additionally, both HIT and RT promote more benefits versus CT to improve body composition, cardiovascular and metabolic parameters.